Cardiac assessment of the elite athlete: Separating structural disease from adaptive changes - Tolani, S.; Schwartz, A. (Structural Heart, 2020)
Sudden cardiac death (SCD) in athletes is a rare event, but it is the number one cause of medical mortality during sport and the sentinel cases of SCD in athletes through the years have made the cardiac assessment of young athletes at the elite level of paramount importance [1]. It is difficult to know the true prevalence as studies differ greatly and can vary in different age groups, ethnicities and athletic populations[2-5]. The Minnesota study on young athletes estimated 1:200,000 death per individual participants per academic year with the majority of deaths (36%) attributed to hypertrophic cardiomyopathy and with the second most prevalent cause being coronary anomalies (17%)[6]. Harmon et. al showed higher rates, reporting in NCAA athletes an overall incidence of 1.37 cases of SCD per 100,000 person years, which was further increased in black athletes at 5.65 per 100,000 person years and as high as 31.99 per 100,000 person years in Division 1 basketball players [7]. Complicating the evaluation of elite athletes is that intense training induces adaptive changes to cardiac chambers, wall thickness and electrocardiogram, known as athlete`s heart, which may be difficult to distinguish from cardiomyopathy. It is important to identify those who have more pronounced cardiac changes, in the so-called gray zone, as these athletes require a more comprehensive examination. Here we will review the current data and expert guidelines on the cardiac assessment of elite athletes (athletes competing at college, international or professional level) including screening, echocardiography and advanced imaging and provide a clinical framework for decision making with regards to determining eligibility for competitive play. Arrythmia and coronary disease in athletes are beyond the scope of this review.